(NmEVDURE^NYE LAND[AFTY SREDNERUSSKOJ LESOSTEPI (B/s - (NmILXKOW(B, (NfEDOR nIKOLAEWI^s; (NzATULEJ(B, (Nk(B.(Ns(B.s; (NrQZANCEW(B, (Nw(B.(Nk(B.s ((NwORONEV (B:s (NiZD(B-(NWO wORONEV(B. (NUN(B-(NTA(B,s, 1990)
(NbIBLIOGR(B.: (NS(B. 221-223s
(NaWT(B. (NUKAZANY W OGL(B.s
Keywords: (NgEOGRAFI^ESKIE LAND[AFTYs